Analyzing receptor assemblies in the cell membrane using fluorescence anisotropy imaging with TIRF microscopy. - Miklos Erdelyi; Joseph Simon; Eric A Barnard; Clemens F Kaminski (PLoS ONE)
Signaling within and between animal cells is controlled by the many receptor proteins in their membrane. They variously operate as trans-membrane monomers and homo- or hetero-dimers, and may assemble with ion-channels: analyses thereof are needed in studies of receptor actions in tissue physiology and pathology. Interactions between membrane proteins are detectable when pre-labeled with fluorophores, but a much fuller analysis is achievable via advanced optical techniques on living cells. In this context, the measurement of polarization anisotropy in the emitted fluorescence has been the least exploited. Here we demonstrate its methodology and particular advantages in the study of receptor protein assembly. Through excitation in both TIRF and EPI fluorescence illumination modes we are able to quantify and suppress contributions to the signal from extraneous intra-cellular fluorescence, and we show that the loss of fluorescence-polarization measured in membrane proteins reports on receptor protein assembly in real time. Receptor monomers and homo-dimers in the cell membrane can be analyzed quantitatively and for homo-dimers only a single fluorescent marker is needed, thus suppressing ambiguities that arise in alternative assays, which require multiple label moieties and which are thus subject to stoichiometric uncertainty.